Pengaruh Penguasaan Konsep Matematika dan Kreativitas Belajar terhadap Perilaku Disiplin - Seruni Seruni (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
The general objective of this research is to discover and analyze empirically the influence of mastery learning math concepts and creativity together to discipline behavior. Affordable population in this study was student of mathematics university fourth semester regular morning Indraprasta PGRI South Jakarta. 100 samples are obtained through a multi- stage random sampling method. The research design used through correlation techniques with three variables consisting of two independent variables, namely mastery of mathematical concepts and creativity in learning as well as the dependent variable, namely behavioral discipline. Data was collected through questionnaire techniques (variable learning creativity and disciplined behavior) and engineering tests (variable mastery of mathematics concepts). The collected data were then analyzed using correlation and multiple regression techniques. Before the data were analyzed, first performed descriptive statistical analysis and test data requirements (normality test, linearity, and multicollinearity test). The results showed that: there is a significant influence mastery of mathematical concepts and creativity to learn the discipline of behavior, with a correlation coefficient of 0.781 and 0.610 coefficient of determination or 61 % mastery learning math concepts and creativity jointly influence the behavior of the discipline. The resulting regression equation y = 42.693 + 0.279X1 + 0.505X2. This may imply that the higher a person's mastery of mathematical concepts the better the behavior of the higher discipline and creativity to learn the higher discipline behavior.